2010
DOI: 10.1111/j.1470-6431.2010.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Materialism and conspicuous consumption in China: a cross‐cultural examination

Abstract: With the growing rise in consumer spending and economic power in Asian societies, it is increasingly important to explore the implications of these developments on consumer culture. This cross-cultural study first discusses the rise of materialism and conspicuous consumption in post-revolution China then examines differences in these phenomena between young adult consumers, aged 18-35, living in urban China and the United States. Utilizing survey data from over 600 respondents, significant differences were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
173
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(187 citation statements)
references
References 44 publications
11
173
0
3
Order By: Relevance
“…Hedonic shopping orientations and materialism are on the rise in China (Podoshen et al, 2011;Davis, 2013). However, a materialistic world view is apparently contradictory to sustainability.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Hedonic shopping orientations and materialism are on the rise in China (Podoshen et al, 2011;Davis, 2013). However, a materialistic world view is apparently contradictory to sustainability.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The results from the mean value of various groups indicated that students without religion exhibited more materialism and low environmental and people-centered values, and TBL (planet and people) than students with religion (H6), consistent with earlier studies [51]. Also, materialism increased with each year of education (1 st yr. -final yr. = 3.520 -4.467), as well as family income (lowest to highest: 3.379 -3.974), confirming that each passing year adds to materialism and negatively influence pro-social attitudes and behaviors (H5) [21], [60]- [62]. For corroboration, the two-sample t-test was conducted to assess the links between demographics, materialism, environmental and people-centered values and TBL.…”
Section: Independent Two-sample T-testmentioning
confidence: 83%
“…In China, the X-Generation (aged 18-35 years with high education and income) has a great preference for foreign products and values (Zhang & Shavitt, 2003). They report higher on materialistic values and conspicuous consumption than the western young adults (Podoshen, Li, & Zhang, 2011), and are more materialism than their parents generation (Gu & Huang, 2009), which drives the increasingly interests on luxury products and fashion. According to the report by WLA, the major consumers of luxury products in China are becoming younger as the new generation shifts their attitude toward life, and people aged between 25 and 30 will become the dominant group of consumers for luxury products in China (Debnam & Svinos, 2006).…”
Section: Demographic Characteristicsmentioning
confidence: 99%